1993
DOI: 10.3109/08982109309150744
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Lipid Vesicles: A Model for Archaeobacteria Membranes

Abstract: In this work we report the results of experiments performed on vesicles of bipolar lipids extracted from the thermophilic archaeobacterium Sulfolobus solfataricus. These results are compared with similar data obtained with synthetic compounds which mimic the structure of natural archaeobacterial lipid molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Perhaps, through the dynamic structural change demonstrated in this study, the plasma membrane of S. acidocaldarius, where PLFE is the major component, begins to gain sufficient "fluidity" for functionality (In't Veld et al, 1992;Elferink et al, 1993) at ϳ48°C. Interestingly, this temperature is close to the minimum growth temperature of thermoacidophilic archaebacteria (ϳ50°C) (Gliozzi and Relini, 1996). This point may be of fundamental importance in understanding the structure-function relationship of archaebacterial membranes and may help the development of bipolar tetraether liposomes for applications in biotechnology.…”
Section: Structural and Functional Implicationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Perhaps, through the dynamic structural change demonstrated in this study, the plasma membrane of S. acidocaldarius, where PLFE is the major component, begins to gain sufficient "fluidity" for functionality (In't Veld et al, 1992;Elferink et al, 1993) at ϳ48°C. Interestingly, this temperature is close to the minimum growth temperature of thermoacidophilic archaebacteria (ϳ50°C) (Gliozzi and Relini, 1996). This point may be of fundamental importance in understanding the structure-function relationship of archaebacterial membranes and may help the development of bipolar tetraether liposomes for applications in biotechnology.…”
Section: Structural and Functional Implicationsmentioning
confidence: 60%
“…Using the multiexcitation method (Chong et al, 1985), we have determined the average, in-plane, and out-of-plane rotational rates of perylene in PLFE liposomes at various temperatures (20 -65°C). Our data indicate that the rotational motions of perylene in the hydrocarbon regions of PLFE liposomes increase abruptly at ϳ48°C, a temperature close to the minimum growth temperature (ϳ50°C) of thermoacidophilic archaebacteria (Gliozzi and Relini, 1996). Moreover, we have used the perylene fluorescence intensity anomaly to conduct comparative studies of membrane packing between PLFE liposomes and various nonarchaebacterial liposomes and suggested that 1,2-diphytanoyl-sn-glycero-3-phosphocholine (DPhPC) and 1,2-diphytanoyl-sn-glycero-3-phosphoglycerol (DPhPG) liposomes are loosely packed compared to PLFE liposomes.…”
Section: Introductionmentioning
confidence: 71%
“…Bipolarity allows the plasma membrane of this archaeon to be organized in a simple monolayer (De Rosa et al, 1986;Gliozzi et al, 1983). The same basic molecular organization is found when vesicles are formed from these lipids; in fact, the lack of a preferential fracture plane of the membrane is observed (De Rosa et al, 1986;Gliozzi and Relini, 1996). The polar lipid extract (PLE) and several lipid fractions have been isolated and their phases characterized; it was shown that at high temperature in the disordered chain conformation, the unsubstituted glycerol headgroups segregate into the hydrocarbon matrix (Gulik et al, 1985(Gulik et al, , 1988.…”
Section: Introductionmentioning
confidence: 83%
“…Future DSC/PPC studies will employ the hydrolyzed PLFE (i.e., removing sugar and phosphate moieties) and quantify the number and distribution of cyclopentane rings in the PLFE dibiphytanyl chain to further understand the role of lipid structure in the thermodynamic properties of PLFE liposomes. This kind of physical characterization not only sheds light on how the plasma membrane of thermoacidophiles might sustain harsh growth conditions, but could also improve the use and design of archaeal bipolar tetraether (e.g., PLFE) liposomes in technological applications such as crystallization of membrane-bound proteins (47-50) and delivery of drugs, vaccines, and genes (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%